Understanding Teachers' Use Of Humor In The Efl Classroom: A Case Study In Guilin, China - Jiang, Hongji (2024)
Humor, as a complex trans-disciplinary phenomenon involving linguistics, psychology, sociology, and anthropology, has been challenging to establish a clear role in education. Language instructors may consider humor as a teaching tool but not a core of teaching, although researchers and practitioners have verified that humor has multiple functions and benefits in language learning. While its potential for facilitating l2 development and its importance in the lives of l2 users is steadily gaining recognition, but a discrepancy exists between the evidence of humor's benefits and its limited use in practice. Previous studies examined the benefits of the use of humor in language classrooms, but few have queried a deep understanding of the role of humor from teachers’ perspectives. Addressing how and why chinese efl teachers elect to integrate or abstain from using humor in the classroom is imperative to elucidating how localized constructs of appropriateness and efficacy shape instructional choices within sociocultural contexts. This qualitative case study explores the use of humor in chinese efl classes and thus hopes to offer inspiration on the implications of using humor in teaching english. This study purposefully selected three teachers in a private secondary school in guilin, china, based on the teachers’ years of teaching and research convenience. In